The economic characteristics of fertility in Hail region and its impact on population growth - Al-Shamry, Nawal Abdel Aziz (Journal of Humanities & Social Sciences, 2021)
The economic characteristics of the residents of Hail affect the population growth, on the one hand we find that home ownership in terms of rent or ownership affects the level of fertility of wives, and on the other hand the majority of families in the city of Hail own their own dwelling, equivalent to (45.5%) of the population They live in private villas, and (23.6%) live in private apartments, and we find that the residents of popular houses are the highest in the average number of children for residents of villas, and (68.7%) of Hail residents reside in houses consisting of two floors, while (31, 3%) reside in houses consisting of one floor in which the fertility level of husbands and wives is high, the number of rooms in the house also affects fertility levels in terms of the degree of crowding in the house, and the impact of the economic aspect is prominent in the profession of the husband and wife and their monthly income on the fertility level in a way. The higher the income, the fewer the family’s children will be born, and vice versa. In this context, we address the importance of entertainment and their impact on fertility levels, so we find that car ownership and domestic labor affect the fertility level and trends of the husband and wife.